China : a history - Bardoe, Cheryl, 1971- (Abrams Books for Young Readers, 2018)
Chronicles the seven-thousand year evolution of China by examining artifacts from The Field Museum in Chicago. Discusses the traditions and changes over time through each dynasty in China's history.